Designing Application for Online Shopping - Wiganepdo, Suryatno; Hidayat, Rachmat; Noviyan, Rizky Dwi; Pamungkas, K J (Universitas Komputer Indonesia, 2024)
This research aims to design an online store to attract consumers' attention because it can facilitate the buying and selling of products, transactions, and ordering of an item and increase people's interest in online shopping. The waterfall approach was the method used in this research. It is a linear methodology of software development, in which improvement is seen as continuing to trickle down through the stages of design, modeling, execution (construction), and testing as a waterfall. The results show that a quality product design can increase brand awareness and quality because consumers and potentially new consumers trust. In online marketing, it can trigger a business in any field in cyberspace. Therefore, website development is also important for business competition and promotes products from placing orders, seeing what items are sold, product names, prices, and product stock. The conclusions obtained in this study are the design of an attractive and quality online store design plays an important role in attracting buyers and increasing sales of a product. With the help of promoting products online, products can be sold worldwide and increase the seller's profits